High-rate hard carbon negative electrode material and preparation method and application thereof
Through shaping, coating and nitrogen doping technology, high-rate hard carbon negative electrode materials were prepared, which solved the problem of insufficient embedded and desodium-delaying capabilities of existing hard carbon materials in sodium ion batteries, and significantly improved the performance of the battery.
Patent Information
- Application Number
- CN202411595861.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
AI Technical Summary
The existing hard carbon materials have low rapid embedding and desodiumization capabilities in sodium ion batteries, low first-term efficiency and low compaction density, which limits their application and development.
By shaping irregular hard carbon into spherical shape, combining cladding material and nitrogen doping technology, a hard carbon negative electrode material with a highly disordered structure and a large carbon layer spacing was prepared.
It improves the rapid migration ability of the sodium storage site and sodium ions of the material, and significantly improves the battery's magnification, first charge and discharge efficiency, specific capacity and cycling performance.
Smart Images

Figure CN119447249A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a negative electrode material, in particular to a high-rate hard carbon negative electrode material, and also to a preparation method and application thereof, belonging to the technical field of sodium ion batteries. Background Art
[0002] At present, the sodium ion battery industry has formed a negative electrode material system based on hard carbon. Hard carbon materials have abundant pores, which are conducive to improving the performance of batteries. For example, the patent with publication number CN118198309A discloses an asphalt-based hard carbon composite material, which has a core-shell structure, the core-shell structure includes a core and an outer shell layer coated on the outer surface of the core, the core is hard carbon doped with heteroatoms and scandium, and the outer shell layer contains a conductive agent and a fast ion conductor. The patent with publication number CN116477599A discloses a method for preparing a hard carbon negative electrode material, which includes the following steps: (1) mixing phenolic resin hard carbon, an organic carbon source, a heteroatom organic compound, ethanol and water to prepare a dispersion; (2) drying the dispersion of step (1) and pre-carbonizing the dried material; (3) breaking up the pre-carbonized material of step (2) and carbonizing the broken up material; (4) kneading the carbonized material of step (3) and asphalt, and then carbonizing again to prepare the hard carbon negative electrode material.
[0003] However, the hard carbon materials in the prior art have low rapid sodium insertion and removal capabilities, low initial efficiency of about 90%, and low compaction density of only 0.97 g / cm 3 , which limits its application and development. Therefore, it is of great significance to develop a hard carbon material with high initial efficiency, high sodium removal ability and good performance. Summary of the invention
[0004] In view of the shortcomings of the prior art, the first object of the present invention is to provide a high-rate hard carbon negative electrode material. The material has a more highly disordered structure and a larger carbon layer spacing, can provide sodium storage sites, and is conducive to the rapid migration of sodium ions, and has excellent electrochemical performance and strong stability.
[0005] The second object of the present invention is to provide a method for preparing a high-rate hard carbon negative electrode material. The method is simple, low-cost and suitable for industrial production.
[0006] The third object of the present invention is to provide an application of a high-rate hard carbon negative electrode material. When used to prepare pole pieces, it can be stacked in a highly orderly manner, increasing the tortuosity and porosity of the pole pieces, effectively improving the diffusion rate of sodium ions, reducing the polarization internal resistance of the pole pieces, and significantly improving the rate of the battery.
[0007] In order to achieve the above technical objectives, the present invention provides a method for preparing a high-rate hard carbon negative electrode material, which comprises: shaping irregular hard carbon to obtain spherical hard carbon; mixing asphalt and a nitrogen-containing compound and subjecting them to heat treatment to obtain a coating material; and then mixing the spherical hard carbon and the coating material and ball milling them to obtain the obtained material.
[0008] The present invention transforms irregularly shaped hard carbon into a spherical shape through shaping. When it is made into a pole piece, it can be stacked in a highly orderly manner, increasing the tortuosity and porosity of the pole piece, effectively improving the diffusion rate of sodium ions, and reducing the polarization internal resistance of the pole piece. Then, through surface coating, the open pore structure is transformed into a closed pore structure to reduce the specific surface area and increase the embedding of sodium ions, thereby improving the electrochemical properties of the material. Using it as the negative electrode of a sodium ion battery can improve the battery's initial charge and discharge efficiency, specific capacity and cycle performance. The spherical hard carbon is more conducive to coating, and can ensure the uniformity and stability of the coating. In addition, in the process of preparing the coating material, nitrogen doping by adding nitrogen-containing compounds can make the asphalt have a larger carbon layer spacing after high-temperature sintering, and can make the coated carbon material have more sodium storage sites, which is beneficial to the rapid migration of sodium ions.
[0009] As a preferred solution, the particle size of the spherical hard carbon is 4-6 μm.
[0010] As a preferred solution, the shaping is achieved by grinding and kneading through granulation equipment.
[0011] As a preferred solution, the mass ratio of the asphalt to the nitrogen-containing compound is 100:5~1.
[0012] As a preferred solution, the nitrogen-containing compound includes at least one of urea, ammonium carbonate and ammonium nitrate.
[0013] As a preferred solution, the heat treatment conditions are: temperature of 200-300° C. and time of 3-6 hours.
[0014] As a preferred solution, the mass ratio of the spherical hard carbon to the coating material is 100:5~0.5.
[0015] As a preferred solution, the ball milling conditions are: a rotation speed of 100-300 r / min, a ball-to-material ratio of 1:80-300, and a ball milling time of 3-40 h.
[0016] As a preferred solution, the balls used in the ball mill include at least one of zirconia balls, stainless steel balls, and agate balls.
[0017] As a preferred solution, the diameter of the balls used in the ball mill is 0.2-2.5 cm.
[0018] The present invention also provides a high-rate hard carbon negative electrode material, which is prepared by the above method. The hard carbon negative electrode material has excellent electrochemical performance and stability.
[0019] The present invention also provides an application of a high-rate hard carbon negative electrode material, which is used to prepare a negative electrode for a sodium ion battery. The material can significantly improve the initial charge and discharge efficiency, specific capacity and cycle performance of the sodium ion battery.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention makes the hard carbon negative electrode material have a more highly disordered structure and a larger carbon layer spacing through shaping, coating and nitrogen doping, which can provide more abundant sodium storage sites, facilitate the rapid migration of sodium ions, and the material has excellent electrochemical properties and stable structure;
[0022] (2) When the hard carbon negative electrode material provided by the present invention is used to make pole pieces, it can be stacked in a highly orderly manner, increasing the tortuosity and porosity of the pole pieces, effectively improving the diffusion rate of sodium ions, reducing the polarization internal resistance of the pole pieces, significantly increasing the battery rate, and greatly improving the initial charge and discharge efficiency, specific capacity and cycle performance of the sodium ion battery;
[0023] (3) The material preparation method is simple, low-cost, and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0025] Figure 1 The negative electrode materials prepared in each embodiment and comparative example are used in a sodium ion battery and the battery rate discharge capacity retention rate.
[0026] Figure 2 The cycle life of the battery when the negative electrode material prepared in Example 1 is used in a sodium ion battery. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] A preparation process of a high-rate hard carbon negative electrode material comprises the following steps:
[0030] (1) Irregular hard carbon powder is added to a granulating device for grinding and kneading to shape it into spherical hard carbon with a size of 4~6μm after shaping.
[0031] (2) Petroleum asphalt and urea were mixed in a mass ratio of 100:5 and then heat treated to obtain a coating material. The heat treatment temperature was 200 °C and the heat treatment time was 3 h.
[0032] (3) Spherical hard carbon and coating material are added into the ball mill of a planetary ball mill at a mass ratio of 100:5. The rotation speed is controlled at 200 r / min and the ball milling is performed for 12 h. The balls used for ball milling are zirconia balls with a diameter of 0.2 cm. The ball-to-material mass ratio is 1:100, and a carbon-coated and nitrogen-doped hard carbon negative electrode material with an average particle size of 5~7 μm is obtained.
[0033] Preparation of sodium ion batteries:
[0034] (1) The carbon-coated and nitrogen-doped spherical hard carbon negative electrode material prepared above was made into a negative electrode slurry according to the mass percentage of 93% (negative electrode active material): 2% (conductive agent): 1.5% (dispersant): 3.5% (binder), and coated on aluminum foil. The coating surface density on both sides was 130 g / m 2 , compacted density is 1.10g / cm 3 , perform die-cutting and set aside.
[0035] (2) Prepare the positive electrode slurry with a mass ratio of 94% (positive electrode active material): 3% (conductive agent): 3% (binder) for the sodium iron pyrophosphate positive electrode, and apply it on the aluminum foil. The coating surface density on both sides is 320g / m 2 , compacted density is 2.0g / cm 3 , perform die-cutting and set aside.
[0036] (3) The positive and negative electrode sheets are stacked, assembled, baked, injected with liquid, formed, and divided into different capacities to obtain a sodium ion battery.
[0037] Example 2
[0038] The following is another high-rate hard carbon negative electrode material. The specific steps are as follows:
[0039] (1) Irregular hard carbon powder is added to a granulating device for grinding and kneading to shape it into spherical hard carbon with a size of 4~6μm after shaping.
[0040] (2) Petroleum asphalt and ammonium carbonate were mixed in a mass ratio of 100:3 and then heat treated to obtain a coating material. The heat treatment temperature was 200°C and the heat treatment time was 3 h.
[0041] (3) The spherical hard carbon and the coating material were mixed in a planetary ball mill at a mass ratio of 100:3 at a rotation speed of 200 r / min for 12 h to obtain a carbon-coated and nitrogen-doped hard carbon negative electrode material with an average particle size of 5-7 μm. The balls used for ball milling were stainless steel balls with a diameter of 2.0 cm and the ball-to-material mass ratio was 1:80.
[0042] Preparation of sodium ion batteries:
[0043] (1) The carbon-coated and nitrogen-doped spherical hard carbon negative electrode material is made into a negative electrode slurry according to a mass ratio of 93% (negative electrode active material): 2% (conductive agent): 1.5% (dispersant): 3.5% (binder), and coated on aluminum foil. The coating surface density is 130 g / m on both sides. 2 , compacted density is 1.10g / cm 3 , perform die-cutting and set aside.
[0044] (2) The positive electrode sheet of Example 1 and the above-mentioned negative electrode sheet are stacked, assembled, baked, injected, formed, and capacity divided to obtain a sodium ion battery.
[0045] Example 3
[0046] The following is another high-rate hard carbon negative electrode material. The specific steps are as follows:
[0047] (1) Irregular hard carbon powder is added to a granulating device for grinding and kneading to shape it into spherical hard carbon with a size of 4~6μm after shaping.
[0048] (2) Petroleum asphalt and ammonium nitrate were mixed in a mass ratio of 100:5 and then heat treated to obtain a coating material. The heat treatment temperature was 200°C and the heat treatment time was 3 h.
[0049] (3) The spherical hard carbon and the coating material were mixed in a planetary ball mill at a mass ratio of 100:1 at a rotation speed of 200 r / min for 12 h to obtain a carbon-coated and nitrogen-doped hard carbon negative electrode material with an average particle size of 5-7 μm. The balls used for ball milling were agate balls with a diameter of 1 cm, and the ball-to-material mass ratio was 1:150.
[0050] Preparation of sodium ion batteries:
[0051] (1) The carbon-coated and nitrogen-doped spherical hard carbon negative electrode material is made into a negative electrode slurry according to the mass ratio of 93% (negative electrode active material): 2% (conductive agent): 1.5% (dispersant): 3.5% (binder), and coated on aluminum foil. The coating surface density on both sides is 130g / m 2 , compacted density is 1.08g / cm 3 , perform die-cutting and set aside.
[0052] (2) The positive electrode sheet of Example 1 and the above-mentioned negative electrode sheet are stacked, assembled, baked, injected, formed, and capacity divided to obtain a sodium ion battery.
[0053] Comparative Example 1
[0054] (1) The irregular hard carbon powder material is made into a negative electrode slurry according to the mass ratio of 93% (negative electrode active material): 2% (conductive agent): 1.5% (dispersant): 3.5% (binder), and coated on aluminum foil. The coating surface density on both sides is 130g / m 2 , compacted density is 0.95g / cm 3 , perform die-cutting and set aside;
[0055] (2) The positive electrode sheet of Example 1 and the above-mentioned negative electrode sheet are stacked, assembled, baked, injected, formed, and capacity divided to obtain a sodium ion battery.
[0056] Comparative Example 2
[0057] (1) The spherical hard carbon material prepared in Example 1 was made into a negative electrode slurry according to a mass ratio of 93% (negative electrode active material): 2% (conductive agent): 1.5% (dispersant): 3.5% (binder), and coated on aluminum foil. The coating surface density on both sides was 130 g / m 2 , compacted density is 0.95g / cm 3 , perform die-cutting;
[0058] (2) The positive electrode sheet of Example 1 and the above-mentioned negative electrode sheet are stacked, assembled, baked, injected, formed, and capacity divided to obtain a sodium ion battery.
[0059] Comparative Example 3
[0060] (1) The negative electrode material was prepared by the method of Example 1, except that the hard carbon material was not shaped but was directly ball-milled with the coating material to obtain a carbon-coated and nitrogen-doped irregularly shaped hard carbon negative electrode material.
[0061] (2) The carbon-coated and nitrogen-doped irregular-shaped hard carbon negative electrode material is made into a negative electrode slurry according to a mass ratio of 93% (negative electrode active material): 2% (conductive agent): 1.5% (dispersant): 3.5% (binder), and coated on aluminum foil. The coating surface density on both sides is 130 g / m2 , compacted density is 0.98g / cm 3 , perform die-cutting;
[0062] (3) The positive electrode sheet of Example 1 and the negative electrode sheet are stacked, assembled, baked, injected, formed, and capacity divided to obtain a sodium ion battery.
[0063] The sodium ion batteries of Example 1 and Comparative Examples 1 to 3 were placed in a test cabinet and subjected to 0.5C, 1C, 3C and 5C rate performance tests respectively. The results are shown in Figure 1 The 5C rate performance test results are shown in Table 1, where the battery first efficiency ICE (%) is the battery first discharge / first charge.
[0064]
[0065] from Figure 1 As can be seen from Table 1, when the hard carbon negative electrode material prepared by the present invention is used in sodium ion batteries, it also has a discharge capacity retention rate of more than 95% under high rate conditions, while the high rate discharge capacity retention rate of the negative electrode material prepared in the comparative example is significantly reduced, indicating that the modified hard carbon negative electrode material prepared by the present invention has excellent electrochemical properties and can greatly improve the performance of sodium ion batteries.
[0066] The battery prepared in Example 1 of the present invention was subjected to a cycle life test. Figure 2 As shown, under 2C conditions, the battery capacity retention rate can still reach more than 95% after 800 cycles. It can be seen that the modified hard carbon negative electrode material prepared by the present invention has high stability and can significantly improve the battery life.
[0067] Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a high-rate hard carbon negative electrode material, characterized in that: The irregular hard carbon is shaped to obtain spherical hard carbon; asphalt and nitrogen-containing compounds are mixed and heat-treated to obtain a coating material; and the spherical hard carbon and the coating material are mixed and ball-milled to obtain the product.
2. The method for preparing a high-rate hard carbon negative electrode material according to claim 1, characterized in that: The particle size of the spherical hard carbon is 4-6 μm.
3. The method for preparing a high-rate hard carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the asphalt to the nitrogen-containing compound is 100:5~1.
4. The method for preparing a high-rate hard carbon negative electrode material according to claim 1 or 3, characterized in that: The nitrogen-containing compound includes at least one of urea, ammonium carbonate and ammonium nitrate.
5. The method for preparing a high-rate hard carbon negative electrode material according to claim 1 or 3, characterized in that: The heat treatment conditions are: temperature of 200-300° C. and time of 3-6 hours.
6. The method for preparing a high-rate hard carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the spherical hard carbon to the coating material is 100:5~0.
5.
7. The method for preparing a high-rate hard carbon negative electrode material according to claim 1 or 6, characterized in that: The ball milling conditions are: a rotation speed of 100-300 r / min, a ball-to-material ratio of 1:80-300, and a ball milling time of 3-40 h.
8. The method for preparing a high-rate hard carbon negative electrode material according to claim 7, characterized in that: The balls used in the ball mill include at least one of zirconia balls, stainless steel balls and agate balls; the diameter of the balls is 0.2-2.5 cm.
9. A high-rate hard carbon negative electrode material, characterized in that: Prepared by the method described in any one of claims 1 to 8.
10. The use of a high-rate hard carbon negative electrode material according to claim 9, characterized in that: Used to prepare negative electrodes for sodium ion batteries.
Citation Information
Patent Citations
Hard carbon negative electrode material and preparation method and application thereof
CN116477599A
Asphalt-based hard carbon composite material, preparation method thereof, battery negative electrode and battery
CN118198309A